2012
DOI: 10.7860/jcdr/2012/4826.2636
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of the Hepatitis B Core Antibody and the Occult Hepatitis B Infection Among Voluntary Blood Donors in Chennai, India

Abstract: Introduction:The infection with the Hepatitis B Virus (HBV) is a global health problem which affects 2 billion people worldwide. In India, the prevalence of the Hepatitis B infection is 4% in the general population. The prevalence of the HBV infection in voluntary blood donors is 1-3%. It has been reported that the viraemia continues even after the clinical recovery from the acute HBV infection. Some blood donors who were negative for the surface antigen but positive for the core antibody have been reported to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…We examined 800 HBsAg negative sera obtained from healthy blood donors and found that 12.37% of them were positive for anti-HBc, which is comparable to two previous Egyptian studies with a prevalence of 14.2% and 10.9% of HBsAg negative volunteer blood donors [1,17]. The study is also comparable to the older anti-HBc prevalence rates reported among HBsAgnegative blood donors in India; 10.01% [9] and 11.2% in Syria [10], respectively.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We examined 800 HBsAg negative sera obtained from healthy blood donors and found that 12.37% of them were positive for anti-HBc, which is comparable to two previous Egyptian studies with a prevalence of 14.2% and 10.9% of HBsAg negative volunteer blood donors [1,17]. The study is also comparable to the older anti-HBc prevalence rates reported among HBsAgnegative blood donors in India; 10.01% [9] and 11.2% in Syria [10], respectively.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, limited-resources developing countries cannot implement NAT for screening of all donors collected blood and are relying on proper donor selection which is complemented by sensitive cost effective serological screening tests to exclude the transmission of infective agents [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 0.83% of the samples were positive for HBsAg which is similar to other Indian studies [ 18 , 19 ]. However, the prevalence of anti-HBc (22.81%) was higher than most of the other studies across the country, where prevalence is reported between 0 and 15% [ [20] , [21] , [22] , [23] , [24] ].…”
Section: Discussionsupporting
confidence: 92%
“…Their results were dierent compared to our studies due to dierent diagnostic methods used. 16 Similarly, another study done in Eastern India showed a prevalence of 17.8 per cent, which is lower than our results. 17 Their study population was HIVinfected patients, and using tenofovir as ARV therapy could be the reason for the lower prevalence.…”
Section: Discussioncontrasting
confidence: 88%